Testing Theories of Discount House Portfolio Selection - Courakis, A. S. (Review of Economic Studies, 1975)
Journal Article Testing Theories of Discount House Portfolio Selection Get access A. S. Courakis A. S. Courakis Oxford University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 42, Issue 4, October 1975, Pages 643–648, https://doi.org/10.2307/2296801 Published: 01 October 1975